2016
DOI: 10.1016/j.rse.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the performance of the Landsat 8/OLI land surface reflectance product

Abstract: The surface reflectance, i.e., satellite derived top of atmosphere (TOA) reflectance corrected for the temporally, spatially and spectrally varying scattering and absorbing effects of atmospheric gases and aerosols, is needed to monitor the land surface reliably. For this reason, the surface reflectance, and not TOA reflectance, is used to generate the greater majority of global land products, for example, from the Moderate Resolution Imaging Spectroradiometer (MODIS) and Visible Infrared Imaging Radiometer Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
682
1
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,239 publications
(708 citation statements)
references
References 34 publications
5
682
1
20
Order By: Relevance
“…Surface reflectance data were downloaded from USGS/EROS (https:// espa.cr.usgs.gov/); these images were calibrated using the LEDAPS algorithm (Landsat 4-5, 7; Masek et al, 2013), or the L8SR algorithm (Landsat 8; Vermote et al, 2016) and CFmask (Zhu and Woodcock, 2012). For the spring migration season from 1983 to 2015, we processed a total of 242 Landsat surface reflectance scenes from Landsat 4, 5, 7 and 8 ( Fig.…”
Section: Landsat Time Seriesmentioning
confidence: 99%
“…Surface reflectance data were downloaded from USGS/EROS (https:// espa.cr.usgs.gov/); these images were calibrated using the LEDAPS algorithm (Landsat 4-5, 7; Masek et al, 2013), or the L8SR algorithm (Landsat 8; Vermote et al, 2016) and CFmask (Zhu and Woodcock, 2012). For the spring migration season from 1983 to 2015, we processed a total of 242 Landsat surface reflectance scenes from Landsat 4, 5, 7 and 8 ( Fig.…”
Section: Landsat Time Seriesmentioning
confidence: 99%
“…The aerosol inversion relies on the assumed relationship between the surface reflectance in the blue, red, and near-infrared bands, using an algorithm similar to the one used for the MODIS aerosol product. It is described in more detail in [33]. The code is run natively by a FORTRAN program, and, for workflow embedding purposes, a Python wrapper was built around it.…”
Section: Atmospheric Correctionmentioning
confidence: 99%
“…The details of surface reflectance estimation for each surface type are described below. Previous attempts show the possibilities of using MODIS data product for surface parameterization and atmospheric parameters retrieval for instruments like Landsat (similar to GF4) [26,37]. One year (2008) cloud-free MODIS C6 TOA reflectance and corresponding MODIS surface reflectance product (MOD09A1) were collected over the study region as shown in Figure 1.…”
Section: Surface Parameterizationmentioning
confidence: 99%
“…Previous studies show that certain relationships between the surface reflectance at visible channels (0.67 and 0.47 µm) and reflectance at near-infrared/ infrared channels (e.g., 0.86, 1.6, 2.1 and 3.75 µm) can be found for certain surface types depending on instruments [5,6,[38][39][40]. Figure 2 shows an Previous attempts show the possibilities of using MODIS data product for surface parameterization and atmospheric parameters retrieval for instruments like Landsat (similar to GF4) [26,37]. One year (2008) cloud-free MODIS C6 TOA reflectance and corresponding MODIS surface reflectance product (MOD09A1) were collected over the study region as shown in Figure 1.…”
Section: Surface Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation